2003
DOI: 10.1373/49.5.752
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomic Profiling Identifies Serum Proteomic Signatures for Detection of Hepatocellular Carcinoma and Its Subtypes

Abstract: Background: Detection of hepatocellular carcinoma (HCC) in patients with chronic liver disease (CLD) is difficult. We investigated the use of comprehensive proteomic profiling of sera to differentiate HCC from CLD. Methods: Proteomes in sera from 20 CLD patients with ␣-fetoprotein (AFP) <500 g/L (control group) and 38 HCC patients (disease group) were profiled by anionexchange fractionation (first dimension), two types (IMAC3 copper and WCX2) of ProteinChip ® Arrays (second dimension), and time-of-flight mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
139
3
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(147 citation statements)
references
References 24 publications
1
139
3
4
Order By: Relevance
“…The significant proteomic features common to both experiments were considered as suitable candidates for purification and identification. The initial strategy to isolate the peaks of interest was based on the serum fractionation protocol used by Poon et al (2003). The sera were diluted in a buffer designed to disrupt protein/protein interactions (9 M urea and 2% CHAPS, pH 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant proteomic features common to both experiments were considered as suitable candidates for purification and identification. The initial strategy to isolate the peaks of interest was based on the serum fractionation protocol used by Poon et al (2003). The sera were diluted in a buffer designed to disrupt protein/protein interactions (9 M urea and 2% CHAPS, pH 9).…”
Section: Resultsmentioning
confidence: 99%
“…The initial step in the purification of the 6.44, 6.64, 8.94 and 50.7 kDa peaks (based on a method validated by our group previously; Poon et al, 2003) was to dilute the serum (100 ml) threefold in 9 M urea, 50 mM Tris/HCl, pH 9 and 2% CHAPS buffer, and apply it to Q Ceramic HyperD F anion exchange beads (Pall, New York, USA) in spin-cup filters (Pierce, Rockford, Illinois, USA). The proteins that did not bind were collected by centrifugation.…”
Section: Biomarker Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a two-way clustering algorithm, hepatocellular carcinoma was successfully differentiated from chronic liver disease [47]. A further study utilizing reverse-phase protein microarrays demonstrated segregation of primary colorectal cancer from metastatic disease to the liver by a similar clustering algorithm [48].…”
Section: Cluster Analysismentioning
confidence: 99%
“…Artificial neural networks offer a further algorithm, which can be trained to recognize and classify complex patterns. This method has been used to discriminate comprehensive proteomic profiles of sera from cancer patients from individuals without cancer [47].…”
Section: Cluster Analysismentioning
confidence: 99%